THE SPEECH ACTS OF SELLERS AND BUYERS IN THE GELUMBANG VILLAGE MARKET, GELUMBANG DISTRICT, MUARA ENIM REGENCY - Rusni Rusni (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2020)
This study aims to describe the speech acts of sellers and buyers in the Gelumbang Village Market, Gelumbang District, Muara Enim Regency. The method used in this research is the content analysis method. The data source used is a conversation between sellers and buyers in the Gelumbang Village Market, Gelumbang District, Muara Enim Regency. The results obtained from this study are the speech acts that are dominantly used are representative speech acts and the least speech acts used are declarative speech acts. The reason for representative speech acts is more dominant to be used because these speech acts contain a lot of information as well as the submission of something in a buying and selling transaction (bargaining). Based on this research the research results can also be obtained that female sellers and buyers have higher speech levels than those of male sellers and buyers. This has become a characteristic or characteristic of women that is more active and clever in speaking, especially in buying and selling activities that include demand for goods and price quotes for goods in the Gelumbang Village Market, Gelumbang District, Muara Enim Regency than men.